The Role of Blockchain Technology to Solve A Problem Distribution Of Government Assistance Wages Subsidies - Lila Sabrinta (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Many organizations, especially government sector still using centralization-based activites such in the public services. One of the activities organized by the government that requires a touch of blockchain technology is the distribution of assistance wages subsidies (BSU) from the government for Indonesian workers affected by the pandemic Covid-19. Practically , implementation of assistance wages subsidies still met many problems. This paper will overview the role of blockchain to solve a problem distribution government assistance wages subsidies. Using tools such as smart contracs, decentralized apps, interopabiity framework and Government-To-Person (G2P), the distribution of wage subsidies assistance can take place transparently and accurately to reach the beneficiaries.